Fabrication of Carbon Paste Electrode Modified with ZnO Nanoparticles and Nanobentonite for Analysis of Bisphenol A by Cyclic Voltammetric - Febriyana, Andini; Setiarso, Pirim (Indonesian Journal of Chemical Research, 2024)
The Bisphenol A (BPA) is a 2,2-bis(4-hydroxyphenyl) propane compound that is produced on a large scale for industrial applications, particularly in polycarbonate plastics. BPA molecules can migrate from plastics into food if stored at high temperatures and for extended periods. Various methods have been developed for BPA analysis, including cyclic voltammetry. This study focuses on the fabrication and application of a carbon paste electrode (CPE) modified with ZnO nanoparticles and nanobentonite for the analysis of BPA in polycarbonate-based bottled drinking water using cyclic voltammetry. The results showed that the optimal electrode conditions were: electrode composition 3:4:1:2 (carbon: nanobentonite: ZnO nanoparticles: paraffin), and pH 7. The BPA content obtained by cyclic voltammetry for brands A, B, and C was 0.2102; 0.1752; and 0.2210 mM. These results demonstrate that cyclic voltammetry with a ZnO nanoparticle and nanobentonite modified carbon paste electrode can be used for BPA analysis.